ANTIHYPERURICEMIA ACTIVITY OF WUALAE FRUIT (Etlingera elatior Jack R. M. Smith) ETHANOL EXTRACT IN VIVO - Asriullah Jabbar; Wahyuni Wahyuni; Mesi Leorita; Muhammad Ilyas Yusuf; Sahidin Sahidin (Universitas Muhammadiyah Magelang, 2021)
Plants Etlingera elatior (Wualae) is a family Zingiberaceae of ​​the genus Etlingera which has a large population in the world. The E. elatior plant is widely used empirically in the community to increase endurance and seasoning in fruit. In this study, ethanol extract was used to determine its potential and effectiveness as an antihyperuricemia (in vivo) was tested pharmacologically on Rattus novergicus L. In this study, twenty-four rats were grouped into six groups, namely the ethanol extract of wualae fruit at a dose (100 mg/kgBW, 200 mg/kgBW, 300 mg/kgBW, 400 mg/kgBW), and the negative control group Sodium CMC 0 .5%, and the positive control group used Allopurinol 10 mg/kgBW. Furthermore, To increase the value of uric acid levels, the rats were first induced with 250 mg/kgBW Potassium Oxonate via intraperitoneal (i.p). Furthermore, the preparation according to the treatment was given orally one hour later after the administration of potassium oxonate. At the hour (1, 2, 3), the blood was taken intravenously (i.v) through the rat's tail, and then the uric acid level was analyzed with a photometer. All doses used in this study, namely 100, 200, 300, and 400 mg/kgBW, showed that they could reduce uric acid overall. The effective dose used is the dose (300 mg/kgBW, 400 mg/kgBW). This research can be concluded that the ethanol extract of the fruit of Etlingera elatior (Jack) R.M. Smith (Wualae) has potential as an antihyperuricemia (uric acid) and can be developed as a traditional medicine